The method of blitz-psychograms in the management of human resources of the company - Pritvorova, T.P.; Jazykbayeva, B.K.; Tasbulatova , B.K. (BUKETOV BUSINESS REVIEW, 2018)
In this article, the aim of the study was to develop a method of psychography for use in the practice of human resource management based on the basic resources available in the Internet of professional consulting companies. The authors of the article describe the psychogram method as a tool for managing human resources. The method allows the manager to adequately assess the required behavioral competencies of the job seeker, using as a standard the system of basic parameters corresponding to this position. The system of basic parameters is formed on the basis of the method of blitz-psychogram after passing by the effective employees of this firm of professional tests, revealing the character traits, motivation, preferred activities and roles in the team. Applicants who meet the parameters of a psychographic portrait will be internally motivated for this type of activity, which will reduce the risk of early dismissal, increase the effectiveness of training and the effectiveness of other actions in the company's human resources management system. The method of the blitz psychogram proposed by the authors allows us to quickly create the information base of psychological portraits of the company's main posts and use it to select applicants, which in the long term reduces the company's costs, is the prevention of staff turnover, saves money on the professional training of employees, reduces the likelihood of customer dissatisfaction.